PERBANDINGAN MODEL PEMBELAJARAN DAN KEMAMPUAN MATEMATIKA TERHADAP KEMAMPUAN PENYELESAIAN SOAL STOIKIOMETRI - Mahafir La Siu; Achmad Rante Suparman; Christiana Niken Larasati (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2018)
Abstract. This study aims to determine significant differences betweenv TTW and TPS learning model on stoichiometric problem solving ability; (ii) the influence of mathematical ability on the capability to solve stoichiometric problems; (iii) the interaction between the learning model and the mathematical ability of stoichiometric problem-solving capability. This research is experimental research with the 2x2 factorial design. The population in this study is students of class X MIA SMA Negeri 1 Manokwari and sample is students of class X MIA 1 consisting 30 students and X MIA 2 consisting 28 students. The data in the analysis use two way analysis of variance. The conclusions of this study were (i) there was no significant difference in the capability of students to solve stoichiometric problems using TTW and TPS models; (ii) there was a significant difference in the capability to solve stoichiometric problems among learners who have high mathematical skills with low mathematical skills; (iii) there was no interaction between instructional model and mathematical ability to solve stoichiometric problem.Keywords: cooperative learning model type TPS, cooperative learning model type TTW, Mathematical ability